Steady MHD Solutions for Collimated Winds - Trussoni, E.; Sauty, C.; Tsinganos, K.; Vlahakis, N. (Springer, 1999)
A convenient approach to model MHD steady axisymmetric outflows is the so-called self-similar technique wherein the physical variables are factorized and a scaling law is assumed along one of the coordinates. This scaling depends on the astrophysical process under investigation. In this note we summarize all possible self-similar MHD outflow solutions; furthermore, we briefly discuss the main properties of a class of solutions which are self-similar in the meridional direction and allow to analyse in simple terms the dynamical properties of an outflow close to its rotational axis. Special attention is focused on the asymptotic structure of collimated winds. It will be shown that different regimes are possible for jets, in particular they can be either thermally or magnetically confined, depending on the physical conditions of the flow. This analysis is complementary with the well known radial self-similar models which are invoked to study winds from accretion disks.